Marine Bioactive Compounds as Nutraceutical and Functional Food Ingredients for Potential Oral Health - Huang, Yi-Zhen; Jin, Zheng; Wang, Zhe-Ming; Qi, Li-Bo; Song, Shuang; Zhu, Bei-Wei; Dong, Xiu-Ping (Frontiers in Nutrition, 2021)
Oral diseases have received considerable attention worldwide as one of the major global public health problems. The development of oral diseases is influenced by socioeconomic, physiological and traumatic, biological, dietary and hygienic practices factors. Currently, the main prevention strategy for oral diseases is to inhibit the growth of biofilm-producing plaque bacteria. Tooth brushing is the most common method of cleaning plaque, aided by mouthwash and sugar-free chewing gum in the daily routine. As the global nutraceutical market grows, marine bioactive compounds are becoming increasingly popular among consumers for their antibacterial, anti-inflammatory and antitumor properties. However, to date, few systematic summaries and studies on the application of marine bioactive compounds in oral health exist. This review provides a comprehensive overview of different marine-sourced bioactive compounds and their health benefits in dental caries, gingivitis, periodontitis, halitosis, oral cancer, and their potential use as functional food ingredients for oral health. In addition, limitations and challenges of the application of these active ingredients are discussed and some observations on current work and future trends are presented in the conclusion section.